Transcription factor RUNX1 regulates coagulation factor XIII-A (F13A1): decreased platelet-megakaryocyte F13A1 expression and clot contraction in RUNX1 haplodeficiency - Fabiola Del Carpio-Cano; Natthapol Songdej; Liying Guan; Guangfen Mao; Lawrence E. Goldfinger; Jeremy G.T. Wurtzel; Kiwon Lee; Michele P. Lambert; Mortimer Poncz; A. Koneti Rao (Research and Practice in Thrombosis and Haemostasis)
Background: Germline RUNX1 haplodeficiency (RHD) is associated with thrombocytopenia, platelet dysfunction, and predisposition to myeloid malignancies. Platelet expression profiling of an RHD patient showed decreased F13A1, encoding for the A subunit of factor (F)XIII, a transglutaminase that cross-links fibrin and induces clot stabilization. FXIII-A is synthesized by hematopoietic cells, megakaryocytes, and monocytes. Objectives: To understand RUNX1 regulation of F13A1 expression in platelets/megakaryocytes and the mechanisms and consequences of decreased F13A1 in RHD. Methods: We performed studies in platelets, human erythroleukemia (HEL) cells, and human CD34+ cell-derived megakaryocytes including on clot contraction in cells following small inhibitor RNA knockdown (KD) of RUNX1 or F13A1. Results: Platelet F13A1 mRNA and protein were decreased in our index patient and in 2 siblings from an unrelated family with RHD. Platelet-driven clot contraction was decreased in the patient and affected daughter. Promoter studies in HEL cells showed that RUNX1 regulates F13A1 transcription; RUNX1 overexpression increased, and small inhibitor RNA RUNX1 KD reduced F13A1 promoter activity and protein. Following RUNX1 or F13A1 KD, clot contraction by HEL cells was decreased, as were FXIII-A surface expression, myosin light chain phosphorylation, and PAC1 antibody binding upon activation. F13A1 expression and clot contraction were impaired in RUNX1 downregulation in human megakaryocytes. Conclusion: RUNX1 regulates platelet-megakaryocyte F13A1 expression, which is decreased in RHD, reflecting regulation of a coagulation protein by a hematopoietic transcription factor. Platelet and megakaryocyte clot contraction is decreased in RHD, related to multiple impaired mechanisms including F13A1 expression, myosin phosphorylation, and αIIbβ3 activation.